SIAPA YANG LEBIH MERASA ADIL? PEREMPUAN ATAU LAKI-LAKI?: ANALISIS PERBEDAAN PENILAIAN KEADILAN KARYAWAN TINJAUAN DARI SEGI JENIS KELAMIN DI UIN MALANG - Fathul Lubabin Nuqul (lp2m-uin malang, 2008)
Percieve Justice has influence to health, organization commitment, job satisfaction and productivity. In fact most discrimination toward women employees has accurs. But, teoritically, women are more tolerant than men in injustice situation. It is couse in our soceity has sex role, has drived what kind behaviors that does by women and men. The result of the study, reveal significant gender effect were non-existent.Key words: Justice, Gender